LEGAL FRAMEWORK IN IMPLEMENTING THE NATIONAL POLICY ON HIV/AIDS PREVENTION AND CONTROL IN INDONESIAN LOCAL REGULATIONS (UUM Journal of Legal Studies, 2023)
The purpose of this study is to analyze local regulations on the prevention and control of HIVIAIDS and their relevance to the implementation of national policies in Indonesia. More specifically, in light of the absence of a national law on the prevention and control of HIVIAIDS in Indonesia this study discusses the role of local regulation issued by local governments in response to this problem. This study has adopted the doctrinal legal study method and has examined legal materials from a library-based research. This study finds that the existing national policy on HIV/AIDS prevention and control is only substantially specified inthe Regulation of the Ministry of Health No. 21 of 2013, which has been issued to fill the lacunae in legislation on the matter at hand. The Ministerial Regulation has substantively applied the human rights approach to serve as the central government's response and an interpretive guideline for local governments in responding to HIVIAIDS prevention and control issues. The findings also pointed out that local governments are more responsive to the issue, their regulations have underscored the importance of health and human rights as the critical consideration in their policy regarding the prevention and control of HIV/AIDS. Practical recommendations are outlined for the central government to take serious measures to regulate the issues on HIVIAIDS prevention and control at the national level.